2021
DOI: 10.1002/adma.202100489
|View full text |Cite
|
Sign up to set email alerts
|

An Oligonucleotide‐Distortion‐Responsive Organic Transistor for Platinum‐Drug‐Induced DNA‐Damage Detection

Abstract: Organic transistor with DNA‐damage evaluation ability can open up novel opportunities for bioelectronic devices. Even though trace amounts of drugs can cause cumulative gene damage in vivo, the extremely low occurrence proportion makes them hardly transduced into detectable electric signals. Here, an ultrasensitive DNA‐damage sensor based on an oligonucleotide‐distortion‐responsive organic transistor (DROT) is reported by creating controllable conformation change of double‐stranded DNA on the surface of organi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 46 publications
0
11
0
Order By: Relevance
“…(f) Represent signal response of organic transistor with and without oligonucleotide DNA receptor as a function of cisplatin concentration. Reprinted from ref . Copyright 2021 John Wiley and Sons.…”
Section: Key Features Of Natural Materials Enabled Biosensorsmentioning
confidence: 99%
See 3 more Smart Citations
“…(f) Represent signal response of organic transistor with and without oligonucleotide DNA receptor as a function of cisplatin concentration. Reprinted from ref . Copyright 2021 John Wiley and Sons.…”
Section: Key Features Of Natural Materials Enabled Biosensorsmentioning
confidence: 99%
“…When the natural materials with functional groups are adopted as reaction units in OTFTs, outstanding selectivity can be realized due to the formation of chemically active bonds. On the basis of the coordinate bonds between guanine and cisplatin, Di et al reported an oligonucleotide-distortion-responsive organic transistor and realized ultrasensitive single-site DNA damage detection (Figure e,f) . Even when triggered by pM cisplatin, a current response was successfully achieved with a short response time of 20.5 s.…”
Section: Key Features Of Natural Materials Enabled Biosensorsmentioning
confidence: 99%
See 2 more Smart Citations
“…DNA amplification can provide an alternative way to resolve the above issue. 20–22 So far, a variety of signal amplification strategies have been established, such as rolling circle amplification (RCA), 23 loop-mediated amplification 24 and hybridization chain reaction (HCR). 25,26 Among these methods, HCR-based nucleic acid self-assembly signal amplification, a type of toehold mediated strand displacement reaction, has attracted enormous attention due to its simple operation and excellent amplification efficiency.…”
Section: Introductionmentioning
confidence: 99%